Economic Burden Analysis of Parkinson’s Disease Patients in China - Jun-Xiu Yang; Lei Chen (Parkinson's Disease)
Background and Objective. Parkinson’s Disease (PD) is a progressive neurodegenerative disorder, which is prevalent in people over 65 years old. PD reduces patients’ quality of life and exerts a heavy economic burden on patients and their families. The purpose of this research is to identify the costs of PD and to evaluate the economic distribution of medical care for PD patients in China. Methods. A professional survey was administered to 116 patients with PD. Records of medical cost were reviewed. Direct and indirect costs were analyzed. The main cost-driving factors of PD were identified using multivariate regression analysis. Results. The average annual cost per PD patient in China is $3,225.94, with direct and indirect costs accounting for $2,503.46 and $722.48, respectively. Direct costs consist of $556.27 for surgery, $44.67 for appointment fees, $605.67 for prescription medication, $460.29 for hospitalization, $71.03 for auxiliary examination, $35.64 for transportation, $10.39 for special equipment, and $719.50 for formal care. The total cost is closely related to surgical treatment, dopamine agonist, and levodopa costs. Conclusion. The cost of PD patients in China is considerable and exceeds average economic capacity, especially antiparkinson medication and caring costs. This study may provide a reference for PD healthcare optimization in the future.